If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying R(6x + -3) = (4x + 7) Reorder the terms: R(-3 + 6x) = (4x + 7) (-3 * R + 6x * R) = (4x + 7) (-3R + 6xR) = (4x + 7) Reorder the terms: -3R + 6xR = (7 + 4x) Remove parenthesis around (7 + 4x) -3R + 6xR = 7 + 4x Solving -3R + 6xR = 7 + 4x Solving for variable 'R'. Move all terms containing R to the left, all other terms to the right. Reorder the terms: -7 + -3R + -4x + 6xR = 7 + 4x + -7 + -4x Reorder the terms: -7 + -3R + -4x + 6xR = 7 + -7 + 4x + -4x Combine like terms: 7 + -7 = 0 -7 + -3R + -4x + 6xR = 0 + 4x + -4x -7 + -3R + -4x + 6xR = 4x + -4x Combine like terms: 4x + -4x = 0 -7 + -3R + -4x + 6xR = 0 The solution to this equation could not be determined.
| 5n-2(n-2)=-11+3n+5 | | 4y+2=8(y+7) | | 5(-9+x)=-25 | | 6(2+x)=72 | | -2x-30=28-4x | | (3)*(2x+9)=27 | | -8u-30=-6(u+7) | | -3rs(2r^2s+12t-7)= | | -2x-66=62-10x | | 4(x-7)=7x-13 | | K-15=-40 | | -55-2x=-5x+17 | | -5(1+4x)=195 | | 2n+8=3(n-9) | | 3y+18=-6(y-9) | | -31-7x=17-11x | | -3x+5(-9+4x)=-x-4 | | (4)*(3x+12)=64 | | -76+7x=104-2x | | 12x-25=7x+35 | | -4x-14=-7x+12 | | 5x-2(-2x+19)=-83 | | 3(1x+5)=42 | | 8x-68=77+4x | | 3x-6(1+x)=-9x+9 | | 3b-50=4b-74 | | -124+12x=5x+86 | | 9x^2+4x+87=180 | | 6a+70=a | | 8x-151=49-2x | | 5x+3x-9=15 | | 3m^2-7m-40=0 |